2014
DOI: 10.1177/0363546514531396
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Predictors of Early Revision Surgery After Anterior Cruciate Ligament Reconstruction

Abstract: Metal interference screw fixation of a semitendinosus tendon autograft on the tibia was an independent predictor of significantly lower 2-year incidence of revision surgery. Graft selection, graft width, a single-bundle or a double-bundle technique, femoral graft fixation, the injury-to-surgery interval, and meniscus injury were not predictors of early revision surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
106
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(118 citation statements)
references
References 49 publications
9
106
1
2
Order By: Relevance
“…B. die Reduktion von Herz-Kreislauf-Erkrankungen belegt [5]. Darüber hinaus kann Sport im Sinne der Sekundärprävention eine medikamentöse Therapie bei Volkskrankheiten wie der koronaren Herzkrankheit, dem Schlaganfall, der Herzinsuffizienz, dem Diabetes mellitus und der Arthrose zumindest teilweise ergänzen oder gar ersetzen [6] [1,3].…”
Section: Verletzungen Bei Sportlern Neues Zu Diagnostik Und Therapie unclassified
“…B. die Reduktion von Herz-Kreislauf-Erkrankungen belegt [5]. Darüber hinaus kann Sport im Sinne der Sekundärprävention eine medikamentöse Therapie bei Volkskrankheiten wie der koronaren Herzkrankheit, dem Schlaganfall, der Herzinsuffizienz, dem Diabetes mellitus und der Arthrose zumindest teilweise ergänzen oder gar ersetzen [6] [1,3].…”
Section: Verletzungen Bei Sportlern Neues Zu Diagnostik Und Therapie unclassified
“…After revision double-bundle ACL reconstruction, whether a patient was able to resume to performing their physical exercise activity at the pre-injury level was dependent on concomitant cartilage damage and/or meniscal deficiency, which were also critical factors influencing the decision for primary (n=32) or repeated revision (n=8) ACL reconstruction patients to resume to performing their physical exercise activity. Andriolo et al (9) and Andernord et al (15) concluded that patients receiving revision ACL reconstruction patients were less able to resume to the same level of physical exercise activity compared with those receiving primary ACL reconstruction, which may also be associated with the increased concomitant cartilage and/or meniscal injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, inferior outcomes to primary ACL reconstructions were reported, although significant improvements have been demonstrated after revision reconstruction (10)(11)(12)(13)(14). Of note, most revision ACL constructions were performed using a single-bundle technique (15); however, a vast amount of evidence has demonstrated that the double-bundle technique is superior to the single-bundle technique for primary ACL reconstruction (16)(17)(18)(19)(20)(21)(22)(23)(24). Compared with single-bundle ACL reconstruction, the double-bundle technique produced better Lachman and pivot-shift test results, KT arthrometry results and Tegner score after 3-12 years post operation (19).…”
Section: Introductionmentioning
confidence: 99%
“…Using metal interference, screw fixation of semitendinosus tendon autograft on the tibia at the primary ACLR was associated with a lower rate of revision ACLR [6]. The influences of other potential predictors for additional ACLR (such as activity at the time of primary injury, time between injury and primary ACLR, presence of concomitant injuries, and injury side) have not been well studied in large cohorts with multivariable analyses.…”
Section: Predictors For Undergoing An Additional Aclrmentioning
confidence: 99%
“…Keywords: ACL, ACL reconstruction, contralateral, football, functional performance, knee, patient-reported outcome measures, return to sport, return to play, revision, soccer, subsequent injury ISBN: 978-91-7685-736- 6 LIST OF PAPERS Motivation Consist of two parts; intrinsic, which refers to doing an activity for the satisfaction of the activity itself and extrinsic, which refers to doing an activity in order to attain some separable outcome [187] Neuromuscular A complex interaction between the nervous system and control the musculoskeletal system leading to the ability to produce controlled movement through coordinated muscle activity [234] Postural control The act of maintaining, achieving or restoring a state of balance during any posture or activity [173] Introduction…”
mentioning
confidence: 99%